The Bayley-III scale may underestimate neurodevelopmental disability after cardiac surgery in infants. (21st April 2019) - Goldstone, Andrew B; Baiocchi, Michael; Wypij, David; Stopp, Christian; Andropoulos, Dean B; Atallah, Joseph; Atz, Andrew M; Beca, John; Donofrio, Mary T; Duncan, Kim; Ghanayem, Nancy S; Goldberg, Caren S; et al.
Abstract: OBJECTIVES: Neurodevelopmental disability is the most common complication among congenital heart surgery survivors. The Bayley scales are standardized instruments to assess neurodevelopment. The most recent edition (Bayley Scales of Infant and Toddler Development 3rd Edition, Bayley-III) yields better-than-expected scores in typically developing and high-risk infants than the second edition (Bayley Scales of Infant Development 2nd Edition, BSID-II). We compared BSID-II and Bayley-III scores in infants undergoing cardiac surgery. METHODS: We evaluated 2198 infants who underwent operations with cardiopulmonary bypass between 1996 and 2009 at 26 institutions. We used propensity score matching to limit confounding by indication in a subset of patients ( n = 705). RESULTS: Overall, unadjusted Bayley-III motor scores were higher than BSID-II Psychomotor Development Index scores (90.7 ± 17.2 vs 77.6 ± 18.8, P < 0.001), and unadjusted Bayley-III composite cognitive and language scores were higher than BSID-II Mental Development Index scores (92.0 ± 15.4 vs 88.2 ± 16.7, P < 0.001). In the propensity-matched analysis, Bayley-III motor scores were higher than BSID-II Psychomotor Development Index scores [absolute difference 14.1, 95% confidence interval (CI) 11.7–17.6; P < 0.001] and the Bayley-III classified fewer children as having severe [odds ratio (OR) 0.24; 95% CI 0.14–0.42] or mild-to-moderate impairment (OR 0.21; 95% CI 0.14–0.32). The composite of Bayley-III cognitive and language scores was higher than BSID-II Mental Development Index scores (absolute difference 4.0, 95% CI 1.4–6.7; P = 0.003), but there was no difference between Bayley editions in the proportion of children classified as having severe cognitive and language impairment. CONCLUSIONS: The Bayley-III yielded higher scores than the BSID-II and classified fewer children as severely impaired. The systematic bias towards higher scores with the Bayley-III precludes valid comparisons between early and contemporary cardiac surgery cohorts.